AN INTELLECTUAL SYSTEM FOR LEARNING, MONITORING AND EVALUATING KNOWLEDGE - Normatov Nizomiddin Kamoliddin o’g’li; Alday Maqtagүl (Лучшие интеллектуальные исследования, 2023)
Abstract The project is proposed to develop on the basis of methods and tools of artificial intelligence the system of smart-education. Relevance of the research supported by the fact that now is the era of e-learning, which is faster and cheaper than traditional education, but is has poor quality due to the static electronic educational resources and a lack of communication with the students. If we replace static electronic educational resources to the dynamic smart-futors, e-education to smart-education, and computer testing to intelligent system assessment of the knowledge, then the qualtty of e-learning will certainly rise. Today in orn country, e-learning sector is alnost absent; there are only few systems that automate certain processes associated with traditional education. The project will use modern methods of pedagory and psycholory, as well as the methods of mathematical statistics, artificial intelligence, knowledge representation and processing, object-oriented prograrnming. The main expected results are the knowledge base contents of disciplines in a specific specialty and program implementation of smart-education. Implementation results will conduct unitten and oral dialogue for leanring and knowledge assessment without human intervention, to atfact leading professors of the world, to facilitate access to education and to save financial resources, which ultimately gives rise to the high social and economic effects. The potential consumers of the results will be individuals who can works on the Internet and who want to get a second degree, to improve their skills and retrain. The results of the project focused on the creation and processing of knowledge base in the disciplines of a particular specialty. Their implementation will enable citizens to gain free access to smart education. Development of this project may be adding content and implementation of the processing knowledge in the disciplines of new specialties. This will expand the